Correlation Between Authoritarian Parenting and Self-Confidence in School-Age Children in Indonesia: A cross-sectional study - Enggal Hadi Kurniyawan; Rizky Bella Mulyaningsasi; Emi Wuri Wuryaningsih; Lantin Sulistyorini (Nursing and Health Sciences Journal (NHSJ), 2021)
In school-age children, self-confidence is needed to complete the task of psychosocial development, namely industry or the stage of achievement. Which if not implemented correctly, the child will become inferior. Authoritarian parents who often curb and punish can affect a child's self-confidence. This study aimed to analyze the correlation between authoritarian parenting style and self-confidence of school-age children. This study used observational analysis with a cross-sectional approach. The subjects of this study were 96 primary school students who were take using a stratified random sampling technique. Data collection used an authoritarian parenting questionnaire and a self-confidence questionnaire. Data were analyzed using the chi-square test. Analysis results showed that there were 54.2% of respondents who got an authoritarian parenting style, and 45.8% of respondents have low self-confidence. The chi-square test showed a correlation between authoritarian parenting style and self-confidence of school-age children (p-value = 0,001) with OR of 5,211. School-age children who get authoritarian parenting have the risk of experiencing low self-confidence 5,211 times higher. Nurses can provide health education and counseling about good parenting to the parents and teachers.